Comparison of quality of life of schizophrenic patients and healthy people in Rasht - naeima Khodadady; farzaneh shikholeslami; hayedeh mahmuodi; mojgan Baghaie; mahmuod hafezi (Journal of Holistic Nursing and Midwifery)
Introduction: Schizophrenia is a common chronic psychiatric disease which can result in personal-‎social problems. Recently, quality of life (QOL) is considered as an important measure of the ‎impacts of schizophrenia and its treatment, and can be useful in proper planning.‎